An exploration of the influencing factors of privacy fatigue among mobile social media users from the configuration perspective - Wang, Wenjun; Wu, Qikai; Li, Dongqi; Tian, Xinluan (Scientific reports, 2025)
Privacy fatigue caused by privacy data disclose and the complexity of privacy control has become an important factor influencing people’s privacy decision-making behavior. At present, academia mainly studies privacy fatigue as a key determinant to explain the privacy paradox problem, but there is insufficient attention to its influencing factors and specific pathway of occurrence. Exploring the antecedents of privacy fatigue is of great significance for alleviating users’ subjective privacy detachment and promoting privacy protection. Based on the Stressor-Strain-Outcome (SSO) theoretical framework, this study aims to explore the antecedents of privacy fatigue through the qualitative comparative analysis method of fuzzy set (fsQCA). The results show that there are three patterns of pathways which lead to privacy fatigue, namely the rational pattern, emotional pattern, and strain pattern. This study not only provides theoretical reference for understanding the antecedents of privacy fatigue among users but also offers new practical solutions for user privacy management.